1991
DOI: 10.1128/mcb.11.7.3780
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine mutations within the alpha platelet-derived growth factor receptor kinase insert domain abrogate receptor-associated phosphatidylinositol-3 kinase activity without affecting mitogenic or chemotactic signal transduction.

Abstract: A phosphatidylinositol-3 (PI-3) kinase activity of unknown biological function associates with tyrosine kinase-containing proteins, including a number of growth factor receptors after ligand stimulation. In the platelet-derived growth factor (jPDGF) receptor, phosphorylation of a specific tyrosine residue within the kinase insert domain was required for its interaction with this enzyme. We show that substitutions of phenylalanine for tyrosine residue 731 or 742 within the kinase insert domain of the OLPDGF rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 41 publications
3
52
0
2
Order By: Relevance
“…While it is problematic to compare the signaling properties of receptors expressed in different cell lines, studies to date have shown that individually removing PI3K, SHP-2, and PLC␥ does not diminish the ability of the ␣PDGFR to initiate DNA synthesis (15,(68)(69)(70). This sharply contrasts with the observation that removing the binding sites for PI3K, SHP-2, or PLC␥ at least partially affect the ␤PDGFR's ability to transduce a signal to initiate DNA synthesis in most of the cell types tested (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is problematic to compare the signaling properties of receptors expressed in different cell lines, studies to date have shown that individually removing PI3K, SHP-2, and PLC␥ does not diminish the ability of the ␣PDGFR to initiate DNA synthesis (15,(68)(69)(70). This sharply contrasts with the observation that removing the binding sites for PI3K, SHP-2, or PLC␥ at least partially affect the ␤PDGFR's ability to transduce a signal to initiate DNA synthesis in most of the cell types tested (26).…”
Section: Discussionmentioning
confidence: 99%
“…While PI3K, PLC␥, and Src have been shown to be required for initiation of DNA synthesis by the ␤PDGFR, the ␣PDGFR does not seem to require either PI3K or PLC␥ for mitogenic signaling (15,17,30,59,60,68,69). The involvement of Src in ␣PDGFR signal relay has not yet been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Autophosphorylation of the PDGF b-receptor leads to direct binding of phosphatidylinositol 3'-kinase (PI3K), phospholipase C-g (PLC-g), Src family tyrosine kinases, GTPase-activating protein for Ras (RasGAP), the protein tyrosine phosphatase SHP-2, and the adaptor molecules Grb2 and Shc, and the respective binding sites have been identi®ed (Claesson-Welsh, 1994). Among these signal transduction molecules, at least PI3K, PLC-g and SHP-2 also bind to the areceptor (Baznet et al, 1995;Eriksson et al, 1992;Yu et al, 1991). During an analysis of autophosphorylation sites in the a-receptor involved in stimulatory and inhibitory signals for chemotaxis (Yokote et al, 1966), we noticed that Tyr-762 in the receptor is an autophosphorylation site.…”
Section: Introductionmentioning
confidence: 99%
“…Y 731 and Y 742 have been identified as recruitment site for PI3-kinase. 12 Y 1018 and Y 988 have been shown to mediate association with PLC-g1 5 and cCbl. 13 Finally, Y 849 an autophosphorylation site in the activation loop, is required for kinase activity.…”
Section: Introductionmentioning
confidence: 99%